Za človeka gre - Lah, Avguštin (Edinost in dialog, 2025)
Jože Rajhman, in his discussions, focuses on the existential questions of today's man and places him in a relationship with God and God with man. Thus, man's split between being and non-being, between fullness and emptiness, between meaning and meaninglessness, in his paradoxical experience, leads to the experience of God's omnipresence. In every »liminal situation«, and especially in suffering, man is given an encounter with God because man needs God and God needs man. This affirms the fact that God is really »Immanuel«, »God with us«, and God is really God for man and in man. Thus, it becomes evident that God is concerned for man, so that man might be concerned for God and man. God is essentially a Mystery that cannot be magically appropriated and used for individual interests. In a personal decision for God in faith, man perceives the meaning of life and the potential for creating quality interpersonal relationships in society and the Church, and a critical attitude towards social and ecclesiastical institutions.
Keywords: Bog; človek; God; man; osebna vera; paradoks; paradox; personal faith; Rajhman, Jože; suffering; trpljenje